A Study on the Status of Working Conditions of Child Labourers Employed in Hotels and Restaurants of Silchar Town, Assam - Pandiya, Dinesh Kumar; Kumar, Brajesh; Roy, Rajib (Prabandhan: Indian Journal of Management, 2015)
The present study was undertaken to examine the status of the quality of work life of child labourers employed in the restaurants and hotels of Silchar town, Assam. The study considered the following parameters to examine the quality of the work life of the child labourers: (a) the nature and duration of the jobs performed by them, (b) nourishment and health care benefits provided to them, (c) matters related to the monetary and non monetary benefits provided to them. The findings of the present study are alarming and frustrating. The study revealed that the ’future citizens’ of our country are put to work for such jobs in deplorable conditions (cleaning the utensils, tables, and floors; tolerating abuses and reprimands; working for more than 10 hours a day on a remuneration that is less than Rs 50/-a day; having access to little or no medicines when physically indisposed; working for all 7 days of the week; and on the top of all this, taking rest at night on Tables/Combination of benches for less than 6 hours a day). The academicians and researchers need to put these matters on high agenda for a detailed and truthful probing of the matter.